Regeneration method and application of invalid sodium ferric sulfate positive electrode material

By restoring the microstructure and crystal structure of failed sodium ferric sulfate cathode materials through pretreatment, leaching, and regeneration, the high energy consumption and complexity of traditional recycling methods are solved, enabling efficient and low-cost application of recycled materials.

CN120978259APending Publication Date: 2025-11-18CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511178181.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing technologies are insufficient for effectively recovering spent sodium ferric sulfate cathode materials, leading to environmental pollution and resource waste. Meanwhile, traditional methods suffer from high energy consumption, low metal recovery rates, and complex processes.

Method used

By pretreatment to separate aluminum foil, followed by leaching and dissolution treatment, reduction and optimization treatment, and regeneration and carbonization sintering treatment, the failed sodium ferric sulfate cathode material is recovered, its microstructure and crystal structure are restored, and efficient and low-cost regenerated materials are prepared.

Benefits of technology

The resulting regenerated sodium ferric sulfate cathode material exhibits stable crystal structure, excellent chemical sodium storage performance, good cycle stability, meets the requirements of green chemistry, and is suitable for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120978259A_ABST
    Figure CN120978259A_ABST
Patent Text Reader

Abstract

The invention relates to a regeneration method and application of an invalid sodium ferric sulfate positive electrode material, and the regeneration method comprises the following steps: (1) pretreatment: crushing an invalid sodium ferric sulfate positive electrode plate, carrying out ultrasonic stripping, adding the obtained invalid sodium ferric sulfate positive electrode material powder into a carbonic ester solvent, soaking, filtering and drying; (2) leaching treatment: adding a reducing weak acid leaching solution, and heating for reaction; (3) optimization treatment: adding reduced iron powder, a ferrous sulfate source and a sodium sulfate source, stirring and filtering; and (4) regeneration treatment: adding an inorganic carbon source into the obtained filtrate, stirring, spray-drying, sintering in an inert atmosphere, and cooling to obtain the product. A positive pole piece prepared from the regenerated sodium ferric sulfate positive pole material is used for assembling a sodium ion battery. According to the method, the aluminum foil can be recycled, the microstructure and crystal configuration of the obtained material are consistent with those of an original material, and an assembled battery is high in specific discharge capacity, good in cycling stability, simple in process, low in cost and suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for regenerating cathode materials and its application, specifically to a method for regenerating depleted sodium ferric sulfate cathode materials and its application. Background Technology

[0002] Sodium-ion batteries have become an important supplement to lithium-ion batteries due to their abundant resources and low cost. Sodium iron sulfate cathode materials have become a research hotspot in recent years due to their abundant and inexpensive raw material sources, high operating voltage, and high structural stability and safety. However, after long-term cycling, they suffer from capacity decay and phase structure damage, and have had to be abandoned.

[0003] With the widespread use of sodium-ion batteries, the number of expired sodium iron sulfate batteries has been increasing year by year. Because sodium iron sulfate batteries contain chemicals such as sodium perchlorate, inorganic carbon sources, sodium, iron, and sulfate, among which sodium perchlorate has strong oxidizing properties, sulfates easily decompose into SO2 upon heating, and sodium salts easily accumulate, these toxic and harmful substances not only cause serious pollution to the atmosphere, water, and soil, but also endanger human health. The plastic casing, positive and negative electrode materials, and electrolyte in expired sodium iron sulfate batteries all have recycling value. Recycling the sodium iron sulfate positive electrode material from these batteries can not only reduce the environmental pollution caused by waste sodium-ion batteries, but also bring certain economic benefits.

[0004] Currently, existing recycling technologies are mostly aimed at lithium-ion battery materials (such as ternary materials and lithium iron phosphate), while research on the recovery of sodium iron sulfate is relatively limited. Traditional methods (such as high-temperature calcination and strong acid leaching) suffer from problems such as high energy consumption, low metal recovery rate, and wastewater pollution.

[0005] CN119361877A describes a method for recovering sodium ferric sulfate from secondary batteries, sodium ferric sulfate composite materials, positive electrode sheets, and sodium-ion batteries. The method involves mixing a sodium ferric sulfate solution with an alcohol solvent to crystallize and precipitate the sodium ferric sulfate, obtaining a recovered sodium ferric sulfate material. This material is then ball-milled with a conductive agent mixture and subjected to heat treatment to obtain a sodium ferric sulfate composite material. However, this method fails to address additives such as aluminum foil, electrolyte, and PVDF in the positive electrode sheet. These additives can affect the crystal purity of the material in subsequent recycling processes, impacting its application performance. Furthermore, the entire process involves multiple steps, including solution treatment, crystallization, ball milling, and heat treatment, making it complex and requiring sophisticated equipment and operational expertise.

[0006] Therefore, there is an urgent need to develop a method for regenerating spent sodium ferric sulfate cathode materials that can recycle aluminum foil, and whose microstructure and crystal configuration are consistent with the original material. The resulting material has a stable crystal structure, and the assembled battery has excellent chemical sodium storage performance similar to that of the original material. It also has a high discharge specific capacity, good cycle stability, does not involve strong acids / bases, meets the requirements of green chemistry, has a simple process, high feasibility, high efficiency, low cost, and is suitable for industrial application. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for regenerating spent sodium ferric sulfate cathode material and its application. The recycled aluminum foil obtained has the same microstructure and crystal configuration as the original material, the crystal structure is stable, and the assembled battery has similar excellent chemical sodium storage performance as the original material, high discharge specific capacity, good cycle stability, does not involve strong acid / strong alkali, meets the requirements of green chemistry, and has a simple process, high feasibility, high efficiency, low cost, and is suitable for industrial application.

[0008] The technical solution adopted by this invention to solve its technical problem is as follows: A method for regenerating degraded sodium ferric sulfate cathode material, comprising the following steps: (1) Pretreatment: After the failed sodium ferric sulfate positive electrode sheet is broken, the current collector aluminum foil is ultrasonically peeled off, and the obtained failed sodium ferric sulfate positive electrode material powder is added to a carbonate solvent, soaked, filtered, and dried to obtain failed sodium ferric sulfate powder. (2) Leaching treatment: Add a reducing weak acid leaching solution to the expired sodium ferric sulfate powder obtained in step (1), heat and react to obtain a leaching mixture; (3) Optimization treatment: Add reduced iron powder, ferrous sulfate source and sodium sulfate source to the leaching mixture obtained in step (2), mix and stir and then filter to obtain sulfate, iron and sodium ion filtrate; (4) Regeneration treatment: In the sulfate, iron and sodium ion filtrate obtained in step (3), an inorganic carbon source is added and stirred evenly. The resulting regenerated sodium ferric sulfate precursor solution is spray-dried, and the resulting regenerated sodium ferric sulfate precursor powder is sintered under an inert atmosphere and cooled to room temperature in the furnace to obtain the regenerated sodium ferric sulfate cathode material.

[0009] The inventive concept of this invention is as follows: Although spent sodium ferric sulfate cathode material is readily soluble in water, its purity is low due to interference from other chemical substances in the sodium-ion battery system, preventing its direct recycling. This invention utilizes pretreatment separation, leaching dissolution, reduction optimization, and regeneration with carbon sintering processes to recover spent sodium ferric sulfate cathode material for reuse, achieving the goal of recycling and reusing sodium ferric sulfate cathode material.

[0010] Preferably, in step (1), the crushing is performed until it passes through a 2-mesh sieve.

[0011] Preferably, in step (1), the frequency of the ultrasound is 20–40 kHz, and the duration is 0.5–4.0 h (more preferably 1–3 h). Ultrasonic treatment can separate the aluminum foil and the degraded sodium ferric sulfate crystals in the positive electrode sheet. Within the specified parameter range, the degree of separation is moderate, the aluminum foil is not pulverized, facilitating the recovery of the aluminum foil and further processing of the degraded sodium ferric sulfate crystals.

[0012] Preferably, in step (1), the mass-to-volume ratio (kg / L) of the depleted sodium ferric sulfate cathode material powder to the carbonate solvent is 0.1–1.0:1 (more preferably 0.2–0.8:1, and even more preferably 0.3–0.6:1). At this ratio, the added carbonate solvent can effectively soak the cathode material and remove the electrolyte from the depleted sodium ferric sulfate cathode material powder.

[0013] Preferably, in step (1), the soaking temperature is room temperature and the soaking time is 1 to 8 hours (more preferably 2 to 6 hours).

[0014] Preferably, in step (1), the carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene carbonate, or propylene carbonate.

[0015] Preferably, in step (2), the mass-to-volume ratio (kg / L) of the spent sodium ferric sulfate cathode material powder to the reducing weak acid leachate is 0.1–1.0:1 (more preferably 0.2–0.8:1, and even more preferably 0.3–0.6:1). At this ratio, the added reducing weak acid leachate can completely penetrate the spent sodium ferric sulfate powder and dissolve iron and sodium ions. Because an oxide layer exists on the aluminum foil surface, the leaching of residual aluminum impurities can be inhibited.

[0016] Preferably, in step (2), the pH value of the reducing weak acid leachate is 3 to 5. Under this pH condition, the full leaching of iron and sodium ions can be ensured, while the oxidation of ferrous ions is inhibited.

[0017] Preferably, in step (2), the reducing weak acid includes ascorbic acid and / or citric acid, etc.

[0018] Preferably, in step (2), the heating reaction temperature is 50–70°C, and the time is 1–6 h (more preferably 2–5 h). During the heating reaction, due to the moderate temperature, iron ions and sodium ions dissolve from the crystal structure more quickly, resulting in a more thorough leaching effect.

[0019] Preferably, in step (3), reduced iron powder is added until it is not completely dissolved in the leachate.

[0020] Preferably, in step (3), reduced iron powder, ferrous sulfate source, and sodium sulfate source are added, mixed and stirred, and then filtered to obtain a filtrate containing sulfate, iron, and sodium ions. + Fe 2+ and SO4 2- The molar concentrations are all 0.1–10 mol / L (more preferably 1–6 mol / L), and the molar ratios satisfy the chemical formula: Na 2x+2 Fe 2-x (SO4)3, 0≤x≤0.5. Adding reduced iron powder can remove Fe from the filtrate. 3+ All converted to Fe 2+ Then, the residual inorganic carbon, excess reduced iron powder, and other solid impurities such as polyvinylidene fluoride (PVDF) in the leaching mixture are removed by filtration.

[0021] Preferably, in step (3), the ferrous sulfate source includes ferrous sulfate and its hydrate.

[0022] Preferably, in step (3), the sodium sulfate source includes sodium sulfate and its hydrate.

[0023] Preferably, in step (4), the amount of inorganic carbon source used is 1-5% (more preferably 1-3%) of the mass of the spent sodium ferric sulfate cathode material powder. At this amount, the electrochemical performance of the recycled material can be fully utilized, and there will be no side effects due to excessive addition. It also limits the proportion of the cost of inorganic carbon source.

[0024] Preferably, in step (4), the inorganic carbon source includes one or more of conductive carbon black, graphene, or carbon nanotubes.

[0025] Preferably, in step (4), the inlet air temperature for spray drying is 200–250°C (more preferably 220–250°C), and the peristaltic feed rate is 25–65 rpm (more preferably 25–55 rpm). Under these conditions, the sodium and iron ions in the leaching mixture are fully mixed with the inorganic carbon source, resulting in good moisture removal.

[0026] Preferably, in step (4), before sintering, a high-purity nitrogen atmosphere is introduced for 1 to 3 hours to purge the tubular furnace.

[0027] Preferably, in step (4), the sintering treatment refers to: heating from room temperature to 300-500℃ (more preferably 350-480℃) at a rate of 1-10℃ / min, and then holding at that temperature for 1-24 hours (more preferably 12-24 hours). Under these conditions, the precursor powder is fully dehydrated, the crystal structure is stable, and the forming effect is good.

[0028] Preferably, in step (4), the inert atmosphere includes one or more of argon, helium, or nitrogen. Sintering under an inert atmosphere ensures that the sodium ferric sulfate cathode material is not oxidized and maintains ideal electrochemical performance. The protective atmosphere used in the method of this invention is a high-purity atmosphere with a purity ≥99.999%.

[0029] The technical solution adopted by the present invention to further solve its technical problem is as follows: an application of a failed sodium ferric sulfate positive electrode material, wherein the positive electrode sheet made of the regenerated sodium ferric sulfate positive electrode material obtained by the regeneration method of the failed sodium ferric sulfate positive electrode material is used to assemble button, cylindrical, square or pouch sodium-ion batteries.

[0030] The beneficial effects of the method of the present invention are as follows: (1) The aluminum foil recovery rate of the method of the present invention is >65%, and the microstructure and crystal configuration of the obtained recycled sodium ferric sulfate cathode material are consistent with those of the original material, and the crystal structure is stable; (2) The sodium-ion battery assembled from the positive electrode sheet made of the recycled sodium ferric sulfate positive electrode material obtained by the method of the present invention has the following characteristics: at a charge / discharge voltage of 2.0-4.5V and a rate of 0.1C (11mA / g), the initial charge and discharge specific capacities are as high as 102.30mAh / g and 91.77mAh / g, respectively, with a coulombic efficiency of 89.71%. The initial charge and discharge specific capacities are equivalent to 100.61% and 97.95% of the original material, respectively. At a rate of 1C (110mA / g), starting from the 4th cycle, the discharge specific capacity is as high as 88.82mAh / g, equivalent to the original material. The regenerated sodium iron sulfate cathode material obtained by the present invention has a high specific capacity of 97.59%, and the charge and discharge specific capacities after 100 cycles are as high as 85.39 mAh / g and 84.69 mAh / g, respectively. The coulombic efficiency is as high as 99.18%, and the charge and discharge specific capacities are equivalent to 98.66% and 98.27% of the original material, respectively. The discharge specific capacity retention rate after 100 cycles is as high as 95.35%, which is equivalent to 100.69% of the original material. This indicates that the sodium-ion battery assembled with the cathode sheet made of the regenerated sodium iron sulfate cathode material obtained by the present invention has similar excellent chemical sodium storage performance to the original material, high discharge specific capacity, and good cycle stability. (3) The method of the present invention does not involve strong acid / strong alkali, and there is almost no loss of sodium ferric sulfate, which meets the requirements of green chemistry. The process is simple, feasible, efficient, and the raw material cost is low, making it suitable for industrial application. The method of the present invention solves the problems of low value, difficulty in recycling, and easy environmental pollution after the failure of sodium ferric sulfate cathode material. It restores the original electrochemical activity of sodium ferric sulfate cathode material, so that sodium ferric sulfate cathode material can be repeatedly regenerated and reused. Attached Figure Description

[0031] Figure 1The images are SEM images of sodium ferric sulfate cathode material (a) from Reference Example 1, the regenerated sodium ferric sulfate cathode materials (b) and (c) obtained from Examples 1 and 2 of the present invention, and the regenerated sodium ferric sulfate cathode materials (d), (e) and (f) obtained from Comparative Examples 1 to 3. Figure 2 The XRD comparison diagrams are of the sodium ferric sulfate cathode material obtained in Reference Example 1, Examples 1 and 2 of the present invention and Comparative Examples 1 to 3; Figure 3 The first charge and discharge curves of the battery assembled from the positive electrode sheet made of sodium ferric sulfate positive electrode material in Example 1 and the recycled sodium ferric sulfate positive electrode material obtained in Examples 1 and 2 of this invention are shown. Figure 4 The circuit curves are shown for batteries assembled from positive electrode sheets made of sodium ferric sulfate positive electrode material obtained in Examples 1 and 2 of this invention. Detailed Implementation

[0032] The present invention will be further described below with reference to the embodiments and accompanying drawings.

[0033] The protective atmosphere used in the embodiments and comparative examples of this invention is a high-purity atmosphere with a purity of ≥99.999%; the raw materials or chemical reagents used in the embodiments and comparative examples of this invention, unless otherwise specified, are obtained through conventional commercial channels.

[0034] Reference Example 1 This reference example uses commercially available sodium ferric sulfate cathode material, with the molecular formula Na. 2.6 Fe 1.7 (SO4)3 was purchased from Hunan Sodium Energy Era Technology Development Co., Ltd.

[0035] like Figure 1 As shown in (a), the morphology of the sodium ferric sulfate cathode material is micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface.

[0036] like Figure 2 As shown, the crystal structure of this sodium ferric sulfate cathode material is similar to that of Na. 2.5 Fe 1.75 The characteristic peaks of the (SO4)3 standard card (PDF#97-025-2404) are a perfect match.

[0037] A battery assembled from a positive electrode sheet made of sodium ferric sulfate positive electrode material (containing 700g of aluminum foil per kg) was operated at a rate of 2.0–4.5V and 0.1C (11mA / g). When the discharge specific capacity retention rate was less than 80%, it was considered to be in failure. The ineffective sodium ferric sulfate positive electrode sheet was used as the recycled raw material in this embodiment of the invention.

[0038] Example 1: A method for regenerating depleted sodium ferric sulfate cathode material (1) Pretreatment: 2 kg of expired sodium ferric sulfate positive electrode sheet was crushed to pass through a 2-mesh sieve and ultrasonicated at 20 kHz for 2 h. 1116 g of current collector aluminum foil was peeled off (aluminum foil recovery rate was 79.7%). The obtained 476 g of expired sodium ferric sulfate positive electrode material powder was added to 1 L of dimethyl carbonate, soaked at room temperature for 4 h, filtered, and dried to obtain expired sodium ferric sulfate powder. (2) Leaching treatment: 1L of ascorbic acid leaching solution with pH value of 3 was added to the expired sodium ferric sulfate powder obtained in step (1), and the mixture was heated at 60°C for 2 hours to obtain a leaching mixture. (3) Optimization treatment: In the leaching mixture obtained in step (2), reduced iron powder is added until it is not completely dissolved in the leaching solution. At the same time, ferrous sulfate heptahydrate and anhydrous sodium sulfate are added. After mixing and stirring, the mixture is filtered to obtain a sulfate, iron, and sodium ion filtrate (wherein, 2.0 mol / L < n(Na)). + )<2.6mol / L, 1.7mol / L<n(Fe 2+ <2.0 mol / L, n(SO4) 2- The concentration of Na is 3 mol / L, and it satisfies the chemical formula: Na 2x+2 Fe 2-x (SO4)3, 0≤x≤0.5). (4) Regeneration treatment: 5.0g of carbon nanotubes were added to the sulfate, iron and sodium ion filtrate obtained in step (3), and after stirring evenly, the obtained regenerated sodium iron sulfate precursor solution was spray-dried at an air inlet temperature of 220℃ and a peristaltic feed rate of 35rpm. The obtained regenerated sodium iron sulfate precursor powder was then loaded into a corundum magnetic boat and placed in a tube furnace. A high-purity nitrogen atmosphere was first introduced for 2h, and the tube furnace was vented. Then, sintering treatment was carried out under a high-purity nitrogen atmosphere: the temperature was raised from room temperature to 400℃ at a rate of 2℃ / min, and then kept at that temperature for 12h. The furnace was then cooled to room temperature to obtain the regenerated sodium iron sulfate cathode material.

[0039] like Figure 1 As shown in (b), the morphology of the regenerated sodium ferric sulfate cathode material obtained by the method embodiment of the present invention is micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface, indicating that the microstructure of the regenerated sodium ferric sulfate cathode material obtained by the method of the present invention is almost identical to that of the original sodium ferric sulfate cathode material.

[0040] like Figure 2 As shown, the crystal structure of the regenerated sodium ferric sulfate cathode material obtained in the embodiments of the present invention is similar to that of Na. 2.5 Fe 1.75The typical characteristic peaks of the (SO4)3 standard card (PDF#97-025-2404) are perfectly matched, that is, consistent with the crystal structure of the original sodium ferric sulfate cathode material. This indicates that after recycling and regeneration by the method of this invention, the crystal structure of the sodium ferric sulfate cathode material is restored to its original state, thus ensuring the stable performance of the material's electrochemical activity. At the same time, no impurity peaks of organic carbon sources were found, indicating that the added organic carbon sources and their sintering byproducts do not affect the crystal structure of the regenerated sodium ferric sulfate cathode material.

[0041] Application Example 1 of a Degraded Sodium Ferric Sulfate Cathode Material The positive electrode sheet made from the regenerated sodium ferric sulfate positive electrode material obtained in the method embodiment of the present invention is used to assemble a coin cell sodium-ion battery.

[0042] The preparation method of the positive electrode sheet is as follows: Weigh 0.8g of the regenerated sodium ferric sulfate positive electrode material obtained in the embodiment of the present invention, add 0.1g of conductive carbon black SP as a conductive agent and 0.1g of PVDF polyvinylidene fluoride as a binder, and use N-methylpyrrolidone as a solvent, mix and grind to obtain the positive electrode material.

[0043] The battery assembly method is as follows: the above-mentioned positive electrode material is coated on the surface of aluminum foil to form an electrode sheet. Then, in a sealed glove box filled with an inert atmosphere, the electrode sheet is used as the positive electrode, a sodium metal sheet is used as the negative electrode, a glass fiber membrane is used as the separator, and 1 mol / L NaClO4 / EC:DMC (volume ratio 1:1) containing 5.0% FEC is used as the electrolyte to assemble a CR2032 coin cell.

[0044] Example 2 of a method for regenerating depleted sodium ferric sulfate cathode material (1) Preprocessing: Same as step (1) in Example 1; (2) Leaching treatment: 1L of citric acid leaching solution with pH value of 5 is added to the expired sodium ferric sulfate powder obtained in step (1), and the mixture is heated at 70°C for 5 hours to obtain a leaching mixture. (3) Optimization process: Same as step (3) in Example 1; (4) Regeneration treatment: 5.0g of carbon nanotubes were added to the sulfate, iron and sodium ion filtrate obtained in step (3), and after stirring evenly, the obtained regenerated sodium iron sulfate precursor solution was spray-dried at an air inlet temperature of 250℃ and a peristaltic feed rate of 55rpm. The obtained regenerated sodium iron sulfate precursor powder was then loaded into a corundum magnetic boat and placed in a tube furnace. A high-purity nitrogen atmosphere was first introduced for 2h, and the tube furnace was vented. Then, sintering treatment was carried out under a high-purity nitrogen atmosphere: the temperature was raised from room temperature to 350℃ at a rate of 5℃ / min, and then kept at that temperature for 24h. The furnace was then cooled to room temperature to obtain the regenerated sodium iron sulfate cathode material.

[0045] like Figure 1As shown in (c), the morphology of the regenerated sodium ferric sulfate cathode material obtained by the method embodiment of the present invention is micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface, indicating that the microstructure of the regenerated sodium ferric sulfate cathode material obtained by the method of the present invention is almost identical to that of the original sodium ferric sulfate cathode material.

[0046] like Figure 2 As shown, the crystal structure of the regenerated sodium ferric sulfate cathode material obtained in the embodiments of the present invention is similar to that of Na. 2.5 Fe 1.75 The typical characteristic peaks of the (SO4)3 standard card (PDF#97-025-2404) are perfectly matched, that is, consistent with the crystal structure of the original sodium ferric sulfate cathode material. This indicates that after recycling and regeneration by the method of this invention, the crystal structure of the sodium ferric sulfate cathode material is restored to its original state, thus ensuring the stable performance of the material's electrochemical activity. At the same time, no impurity peaks of organic carbon sources were found, indicating that the added organic carbon sources and their sintering byproducts do not affect the crystal structure of the regenerated sodium ferric sulfate cathode material.

[0047] Example 2 of the application of a degraded sodium ferric sulfate cathode material The positive electrode sheet made from the regenerated sodium ferric sulfate positive electrode material obtained in the method embodiment of the present invention is used to assemble a coin cell sodium-ion battery.

[0048] The preparation method of the positive electrode sheet is the same as in Application Example 1.

[0049] The battery assembly method is the same as in Application Example 1.

[0050] Example 3 of a method for regenerating depleted sodium ferric sulfate cathode material (1) Pretreatment: 2 kg of expired sodium ferric sulfate positive electrode sheet was crushed to pass through a 2-mesh sieve and ultrasonicated at 40 kHz for 1 h. 463 g of current collector aluminum foil was peeled off (aluminum foil recovery rate was 66.1%). The obtained 450 g of expired sodium ferric sulfate positive electrode material powder was added to 1.2 L of ethylene carbonate, soaked at room temperature for 3 h, filtered, and dried to obtain expired sodium ferric sulfate powder. (2) Leaching treatment: 1L of ascorbic acid leaching solution with pH value of 4 was added to the expired sodium ferric sulfate powder obtained in step (1), and the mixture was heated at 50°C for 3 hours to obtain a leaching mixture. (3) Optimization treatment: In the leaching mixture obtained in step (2), reduced iron powder is added until it is not completely dissolved in the leaching solution. At the same time, ferrous sulfate heptahydrate and anhydrous sodium sulfate are added. After mixing and stirring, the mixture is filtered to obtain a sulfate, iron, and sodium ion filtrate (wherein, 2.0 mol / L < n(Na)). + )<2.6mol / L, 1.7mol / L<n(Fe 2+ <2.0 mol / L, n(SO4)2- The concentration of Na is 3 mol / L, and it satisfies the chemical formula: Na 2x+2 Fe 2-x (SO4)3, 0≤x≤0.5). (4) Regeneration treatment: 5.0g of carbon nanotubes were added to the sulfate, iron and sodium ion filtrate obtained in step (3), and after stirring evenly, the obtained regenerated sodium iron sulfate precursor solution was spray-dried at an air inlet temperature of 235℃ and a peristaltic feed rate of 25rpm. The obtained regenerated sodium iron sulfate precursor powder was then loaded into a corundum magnetic boat and placed in a tube furnace. A high-purity nitrogen atmosphere was first introduced for 3h, and the tube furnace was vented. Then, sintering treatment was carried out under a high-purity nitrogen atmosphere: the temperature was raised from room temperature to 480℃ at a rate of 10℃ / min, and then kept at that temperature for 18h. The furnace was then cooled to room temperature to obtain the regenerated sodium iron sulfate cathode material.

[0051] Upon testing, the morphology of the regenerated sodium ferric sulfate cathode material obtained by the method embodiment of the present invention consists of micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface. This indicates that the microstructure of the regenerated sodium ferric sulfate cathode material obtained by the method of the present invention is almost identical to that of the original sodium ferric sulfate cathode material.

[0052] Upon testing, the crystal structure of the regenerated sodium ferric sulfate cathode material obtained in the embodiments of the present invention is similar to that of Na. 2.5 Fe 1.75 The typical characteristic peaks of the (SO4)3 standard card (PDF#97-025-2404) match the crystal structure of the original sodium ferric sulfate cathode material, indicating that the crystal structure of the sodium ferric sulfate cathode material is restored to its original state after recycling and regeneration using the method of this invention, thus ensuring the stable performance of the material's electrochemical activity. At the same time, no impurity peaks of organic carbon sources were found, indicating that the added organic carbon sources and their sintering byproducts do not affect the crystal structure of the regenerated sodium ferric sulfate cathode material.

[0053] Example 3 of the application of a degraded sodium ferric sulfate cathode material The positive electrode sheet made from the regenerated sodium ferric sulfate positive electrode material obtained in the method embodiment of the present invention is used to assemble a coin cell sodium-ion battery.

[0054] The preparation method of the positive electrode sheet is the same as in Application Example 1.

[0055] The battery assembly method is the same as in Application Example 1.

[0056] Comparative Example 1 The only difference between Comparative Example 1 and Method Example 1 is that in step (1), 2 kg of expired sodium ferric sulfate positive electrode sheet was crushed to pass through a 2-mesh sieve and then sonicated at 20 kHz for 2 hours to peel off 1116 g of current collector aluminum foil (aluminum foil recovery rate of 79.7%), thus obtaining 476 g of expired sodium ferric sulfate powder. That is, in step (1) of this Comparative Example, no carbonate solvent was added for soaking, otherwise it is the same as Method Example 1.

[0057] like Figure 1 As shown in (d), the morphology of the recycled sodium ferric sulfate cathode material obtained in the comparative example of the present invention is micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface, which is consistent with the microstructure of the original sodium ferric sulfate cathode material. This indicates that the material morphology did not change significantly after recycling and regenerating in the comparative example of the present invention.

[0058] like Figure 2 As shown, the crystal structure of the recycled sodium ferric sulfate cathode material obtained in the comparative example of this invention is similar to that of Na... 2.5 Fe 1.75 The typical characteristic peaks of the (SO4)3 standard card (PDF#97-025-2404) match, indicating that the crystal structure is basically consistent with that of the original sodium ferric sulfate cathode material. However, weak impurity peaks are present in the 25–27° range, suggesting that the subsequent processing steps could not completely remove organic matter because the cathode material was not soaked in carbonate solvents.

[0059] The positive electrode sheet made from the recycled sodium ferric sulfate positive electrode material obtained in the comparative example of this invention is used to assemble a coin cell sodium-ion battery.

[0060] The preparation method of the positive electrode sheet is the same as in Application Example 1.

[0061] The battery assembly method is the same as in Application Example 1.

[0062] Comparative Example 2 The only difference between this comparative example and Method Example 1 is that in step (2), 1L of deionized water with a pH of 7 is added to the expired sodium ferric sulfate powder obtained in step (1), and the mixture is heated at 25°C for 12 hours to obtain a leaching mixture. The rest is the same as in Method Example 1.

[0063] like Figure 1 As shown in (e), the morphology of the recycled sodium ferric sulfate cathode material obtained in the comparative example of the present invention is micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface, which is consistent with the microstructure of the original sodium ferric sulfate cathode material. This indicates that the material morphology did not change significantly after recycling and regenerating in the comparative example of the present invention.

[0064] like Figure 2As shown, the characteristic peaks of the recycled sodium ferric sulfate cathode material obtained in the comparative example of this invention are complex and cannot match the typical crystal structure. This indicates that if the pH value is too high or the temperature is too low during the leaching process of the failed sodium ferric sulfate cathode material powder, the reaction will be insufficient and the leaching effect will be unsatisfactory. There is interference from various impurity ions, and the background of the characteristic curve is generally rough, which affects the crystal purity of the recycled sodium ferric sulfate cathode material.

[0065] The positive electrode sheet made from the recycled sodium ferric sulfate positive electrode material obtained in the comparative example of this invention is used to assemble a coin cell sodium-ion battery.

[0066] The preparation method of the positive electrode sheet is the same as in Application Example 1.

[0067] The battery assembly method is the same as in Application Example 1.

[0068] Comparative Example 3 The only difference between this comparative example and method example 1 is that in step (3), ferrous sulfate heptahydrate and anhydrous sodium sulfate are added to the leaching mixture obtained in step (2), and after mixing and stirring, the mixture is filtered to obtain a sulfate, iron, and sodium ion filtrate (n(Na)). + ) = 2.6 mol / L, n(Fe 2+ ) = 1.7 mol / L, n(SO4) 2- (3 mol / L). Same as Example 1.

[0069] like Figure 1 As shown in (f), the morphology of the recycled sodium ferric sulfate cathode material obtained in the comparative example of the present invention is micron-sized spherical or fragmented particles and their aggregates, with carbon nanotubes uniformly coated on the surface, which is consistent with the microstructure of the original sodium ferric sulfate cathode material. This indicates that the material morphology did not change significantly after recycling and regenerating in the comparative example of the present invention.

[0070] like Figure 2 As shown, the crystal structure of the recycled sodium ferric sulfate cathode material obtained in the comparative example of this invention is similar to that of Na... 2.5 Fe 1.75 The peaks of the (SO4)3 standard card (PDF#97-025-2404) match the typical characteristic peaks, indicating that the crystal structure is basically consistent with that of the original sodium ferric sulfate cathode material. However, a weak impurity peak exists between 18 and 27°, which was further confirmed by analysis to be a characteristic peak of the Fe3O4 standard card (PDF#97-026-3012) (marked with "▽" in the figure). This indicates that since no reducing iron powder was added in this comparative example, Fe3O4 was present in the subsequent regeneration process. 3+ Interference from these factors significantly affects the crystal purity of the regenerated sodium ferric sulfate cathode material.

[0071] The positive electrode sheet made from the recycled sodium ferric sulfate positive electrode material obtained in the comparative example of this invention is used to assemble a coin cell sodium-ion battery.

[0072] The preparation method of the positive electrode sheet is the same as in Application Example 1.

[0073] The battery assembly method is the same as in Application Example 1.

[0074] To facilitate comparison of electrochemical performance, the sodium ferric sulfate cathode material of Reference Example 1 was used for cathode preparation and battery assembly according to Application Example 1. Batteries assembled from cathode materials made from the sodium ferric sulfate cathode material of Reference Example 1, and the recycled sodium ferric sulfate cathode materials obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to charge-discharge electrochemical performance tests at 2-4.5V, 0.1C=11mA / g, and 1C=110mA / g. The test results are shown in Table 1 and... Figure 3 , 4 As shown.

[0075] Table 1. Comparison of electrochemical performance test results of batteries assembled from cathode materials made of sodium ferric sulfate cathode material obtained in Reference Example 1 of the present invention, Examples 1-3 of the present invention, and Comparative Examples 1-3.

[0076] As shown in Table 1, the results of Examples 1-3 of the present invention indicate that the initial charge and discharge specific capacity and 100-cycle performance of the sodium ferric sulfate cathode material after recycling and regeneration by the method of the present invention are restored to their original state, approaching or even exceeding those of the original sodium ferric sulfate cathode material. This demonstrates that the regeneration effect of the method of the present invention is significant. The recycling and regeneration by the method of the present invention can restore the original crystal structure and maintain structural stability during charge and discharge, with small volume expansion, good conductivity, and highly reversible charge and discharge reactions.

[0077] Table 1 shows that, according to Comparative Example 1, if dimethyl carbonate is not used to remove the electrolyte in the cathode material during the recycling and regeneration process, the organic matter cannot be completely removed in subsequent processing steps. Comparative Example 2 shows that if the pH of the reducing weak acid leaching solution is too high and the reaction temperature is too low during the recycling and regeneration process, the reaction will be insufficient, the leaching effect will be unsatisfactory, and various impurity ions will interfere, resulting in a rough background on the characteristic curve and affecting the crystal purity of the regenerated sodium ferric sulfate cathode material. Comparative Example 3 shows that if reducing iron powder is not added during the recycling and regeneration process, Fe2+ will be present in the subsequent regeneration process. 3+Interference from the electrolyte can easily lead to the formation of Fe3O4 impurities, which in turn affects the crystal purity of the regenerated sodium ferric sulfate cathode material. This results in limited electrochemical performance of the regenerated sodium ferric sulfate cathode material, significantly lower than that of the sodium ferric sulfate cathode material obtained in Reference Example 1 and Examples 1-3 of this invention. This indicates that during the recycling process, the presence of the electrolyte, the pH value of the reducing weak acid leaching solution, and the reaction temperature, along with the presence of Fe3O4, all significantly influence the electrochemical performance. 3+ Interference from any of these factors can severely affect the charge-discharge process and cycle stability of sodium ferric sulfate.

Claims

1. A method for regenerating spent sodium ferric sulfate cathode material, characterized in that, Includes the following steps: (1) Pretreatment: After the failed sodium ferric sulfate positive electrode sheet is broken, the current collector aluminum foil is ultrasonically peeled off, and the obtained failed sodium ferric sulfate positive electrode material powder is added to a carbonate solvent, soaked, filtered, and dried to obtain failed sodium ferric sulfate powder. (2) Leaching treatment: Add a reducing weak acid leaching solution to the expired sodium ferric sulfate powder obtained in step (1), heat and react to obtain a leaching mixture; (3) Optimization treatment: Add reduced iron powder, ferrous sulfate source and sodium sulfate source to the leaching mixture obtained in step (2), mix and stir and then filter to obtain sulfate, iron and sodium ion filtrate; (4) Regeneration treatment: In the sulfate, iron and sodium ion filtrate obtained in step (3), an inorganic carbon source is added and stirred evenly. The resulting regenerated sodium ferric sulfate precursor solution is spray-dried, and the resulting regenerated sodium ferric sulfate precursor powder is sintered under an inert atmosphere and cooled to room temperature in the furnace to obtain the regenerated sodium ferric sulfate cathode material.

2. The method for regenerating the degraded sodium ferric sulfate cathode material according to claim 1, characterized in that: In step (1), the material is crushed to pass through a 2-mesh sieve; the frequency of the ultrasonication is 20-40 kHz, and the time is 0.5-4.0 h; the mass-to-volume ratio of the degraded sodium ferric sulfate cathode material powder to the carbonate solvent is 0.1-1.0:1 kg / L; the soaking temperature is room temperature, and the time is 1-8 h; the carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, ethylene carbonate, or propylene carbonate.

3. The method for regenerating the degraded sodium ferric sulfate cathode material according to claim 1 or 2, characterized in that: In step (2), the mass-to-volume ratio of the degraded sodium ferric sulfate cathode material powder to the reducing weak acid leachate is 0.1–1.0:1 kg / L; the pH of the reducing weak acid leachate is 3–5; the reducing weak acid includes ascorbic acid and / or citric acid; the heating reaction temperature is 50–70°C, and the time is 1–6 h.

4. The method for regenerating the degraded sodium ferric sulfate cathode material according to any one of claims 1 to 3, characterized in that: In step (3), reduced iron powder is added until it is not completely dissolved in the leachate; reduced iron powder, ferrous sulfate source, and sodium sulfate source are added, mixed and stirred, and then filtered to obtain a filtrate containing sulfate, iron, and sodium ions. + Fe 2+ and SO4 2- The molar concentrations of all components are 0.1–10 mol / L, and the molar ratios satisfy the chemical formula: Na 2x+2 Fe 2-x (SO4)3, 0≤x≤0.5; the ferrous sulfate source includes ferrous sulfate and its hydrate; the sodium sulfate source includes sodium sulfate and its hydrate.

5. The method for regenerating the degraded sodium ferric sulfate cathode material according to any one of claims 1 to 4, characterized in that: In step (4), the amount of inorganic carbon source used is 1-5% of the mass of the spent sodium ferric sulfate cathode material powder; the inorganic carbon source includes one or more of conductive carbon black, graphene, or carbon nanotubes; the inlet air temperature of the spray drying is 200-250℃, and the peristaltic feeding speed is 25-65 rpm; before sintering, a high-purity nitrogen atmosphere is introduced for 1-3 hours to purge the tube furnace; the sintering treatment refers to: heating from room temperature to 300-500℃ at a rate of 1-10℃ / min and holding at that temperature for 1-24 hours; the inert atmosphere includes one or more of argon, helium, or nitrogen.

6. An application of the degraded sodium ferric sulfate cathode material as described in any one of claims 1 to 5, characterized in that: The positive electrode sheet made from the regenerated sodium ferric sulfate positive electrode material obtained by the regeneration method of the failed sodium ferric sulfate positive electrode material according to any one of claims 1 to 5 is used to assemble button, cylindrical, square or pouch sodium-ion batteries.

Citation Information

Patent Citations

  • Recycling method of sodium ferric sulfate in secondary battery, sodium ferric sulfate composite material, positive plate and sodium ion battery

    CN119361877A